1974
DOI: 10.1126/science.185.4156.1058
|View full text |Cite
|
Sign up to set email alerts
|

Sea Otters: Their Role in Structuring Nearshore Communities

Abstract: A comparison of western Aleutian Islands with and without sea otter populations shows that this species is important in determining littoral and sublittoral community structure. Sea otters control herbivorous invertebrate populations. Removal of sea otters causes increased herbivory and ultimately results in the destruction of macrophyte associations. The observations suggest that sea otter reestablishment indirectly affects island fauna associated with macrophyte primary productivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
752
1
5

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 977 publications
(767 citation statements)
references
References 18 publications
(8 reference statements)
9
752
1
5
Order By: Relevance
“…We found that emigration, rather than predation, accounted for about 50% of the reduction in minnow numbers following bass addition to a Campostoma pool (Power et al, 1985). This clear flowing river with its replicated pool habitats facilitated experiments that supported predictions from the trophic cascade model (Estes and Palmisano, 1974;Estes et al, 1978) and theory predicting the stabilizing effects of the differential mobility of predators versus prey through patchy environments (Huffaker, 1958;Hastings, 1977).…”
Section: When Is a Pool A Pool?supporting
confidence: 53%
“…We found that emigration, rather than predation, accounted for about 50% of the reduction in minnow numbers following bass addition to a Campostoma pool (Power et al, 1985). This clear flowing river with its replicated pool habitats facilitated experiments that supported predictions from the trophic cascade model (Estes and Palmisano, 1974;Estes et al, 1978) and theory predicting the stabilizing effects of the differential mobility of predators versus prey through patchy environments (Huffaker, 1958;Hastings, 1977).…”
Section: When Is a Pool A Pool?supporting
confidence: 53%
“…Predation is a process that may have changed through time to change the selection pressures on mussel shell construction. Sea otter (Enhydra lutris) abundance in the Pacific Northwest is known to have decreased markedly over time [55], and there is evidence that they were used and hunted by Native Americans in this region, although their remains are nearly absent in the Sand Point midden [56]. Shell thickness may offer little protection against predation by sea otters, which prey on an entire patch of mussels at once [57].…”
Section: Discussionmentioning
confidence: 99%
“…Some detail of this ecosystem is available in Estes and Palmisano (1974) and Estes et al (1998), only a broad and aggregated picture is used in the simulations. The ecosystem is a food web with four trophic levels illustrated in Figure 2.…”
Section: Numerical Simulationsmentioning
confidence: 99%